Impairment of chaperone‐mediated autophagy leads to selective lysosomal degradation defects in the lysosomal storage disease cystinosis - Gennaro Napolitano; Jennifer L Johnson; Jing He; Celine J Rocca; Jlenia Monfregola; Kersi Pestonjamasp; Stephanie Cherqui; Sergio D Catz (EMBO Molecular Medicine)
Abstract Metabolite accumulation in lysosomal storage disorders (LSDs) results in impaired cell function and multi‐systemic disease. Although substrate reduction and lysosomal overload‐decreasing therapies can ameliorate disease progression, the significance of lysosomal overload‐independent mechanisms in the development of cellular dysfunction is unknown for most LSDs. Here, we identify a mechanism of impaired chaperone‐mediated autophagy (CMA) in cystinosis, a LSD caused by defects in the cystine transporter cystinosin (CTNS) and characterized by cystine lysosomal accumulation. We show that, different from other LSDs, autophagosome number is increased, but macroautophagic flux is not impaired in cystinosis while mTOR activity is not affected. Conversely, the expression and localization of the CMA receptor LAMP2A are abnormal in CTNS‐deficient cells and degradation of the CMA substrate GAPDH is defective in Ctns−/− mice. Importantly, cysteamine treatment, despite decreasing lysosomal overload, did not correct defective CMA in Ctns−/− mice or LAMP2A mislocalization in cystinotic cells, which was rescued by CTNS expression instead, suggesting that cystinosin is important for CMA activity. In conclusion, CMA impairment contributes to cell malfunction in cystinosis, highlighting the need for treatments complementary to current therapies that are based on decreasing lysosomal overload.